1995
DOI: 10.1111/j.1600-0536.1995.tb00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational allergic contact dermatitis in construction workers

Abstract: We report the patch test results of 449 construction workers who came as patients to the Occupational Dermatology Service of the Instituto Nacional de Medicina y Seguridad del Trabajo in Madrid between 1989 and 1993. 90.8% of them were patch tested, because they had cutaneous lesions or a clinical history suggestive of occupational dermatitis. 65.5% (268) of those patch tested showed one or more reactions connected with their work. Chromate at 42.1% was the main allergen, followed by cobalt, 20.5%, nickel, 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 20 publications
5
35
1
2
Order By: Relevance
“…21 Studies from workplaces found exceptionally high rates of ACD from ERS in aircraft manufacturing workers (56%) 7 and marble workers (45%) 22 , amongst others. Skin sensitization is also common amongst construction workers (up to 9.7%) and is caused by ERS present in cement and other building materials, 18,23 but is also frequent in newer settings such as the production of wind turbine rotor blades 15 and relining of old pipes. 13 It can also occur in unexpected settings such as microscopy of histological samples, due to the presence of ERS in the microscopy immersion oil.…”
Section: Introductionmentioning
confidence: 99%
“…21 Studies from workplaces found exceptionally high rates of ACD from ERS in aircraft manufacturing workers (56%) 7 and marble workers (45%) 22 , amongst others. Skin sensitization is also common amongst construction workers (up to 9.7%) and is caused by ERS present in cement and other building materials, 18,23 but is also frequent in newer settings such as the production of wind turbine rotor blades 15 and relining of old pipes. 13 It can also occur in unexpected settings such as microscopy of histological samples, due to the presence of ERS in the microscopy immersion oil.…”
Section: Introductionmentioning
confidence: 99%
“…The surface areas of the patient's fingers and fingertips were 607.0 cm 2 and 100.8 cm 2 , respectively. The working history showed that the patient had a total of 40 working days with SL5510 exposures over 265 normal operation days and 10 working days with SL5510 exposures over the entire abnormal operation days.…”
Section: Exposure and Dose-response Assessmentsmentioning
confidence: 99%
“…Occupational dermatitis occurred mainly in construction, electronics and painting industries [1][2][3][4][5][6] in previous studies but was not reported in the automobile industry before. The cases of allergic contact dermatitis (ACD) in these studies were mainly caused by exposures to epoxy resin [1][2][3][4][5] and related compounds [6][7][8][9] through direct dermal contact, but some studies reported that airborne chemical exposure could also cause ACD [10][11][12][13] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En este sentido, estudios médicos llevados a cabo por el Dr. Conde-Salazar y Col. (8) informaron que dentro de las enfermedades profesionales la Dermatitis Profesional tiene un porcentaje del 70%; por lo tanto, esta enfermedad tiene una incidencia importante y una gran repercusión en la sociedad actual.…”
Section: Introductionunclassified